Anticholinergic Activity in Cerebrospinal Fluid and Serum in Individuals with Hip Fracture with and without Delirium. Issue 1 (2nd January 2014) - Watne, Leiv Otto; Hall, Roanna J.; Molden, Espen; Ræder, Johan; Frihagen, Frede; MacLullich, Alasdair M. J.; Juliebø, Vibeke; Nyman, Armika; Meagher, David; Wyller, Torgeir B.
<x xml:space="preserve">Abstract</x> Objectives To examine whether anticholinergic activity (AA) in cerebrospinal fluid (CSF) and serum is associated with risk of delirium in individuals with hip fracture. Design Prospective cohort study. Setting Two university hospitals in Oslo, Norway, and Edinburgh, UK. Participants Individuals admitted with acute hip fracture (N = 151). Measurements Participants were assessed daily for delirium using the Confusion Assessment Method (preoperatively and postoperative days 1–5 (all) or until discharge (participants with delirium)). Prefracture cognitive function was assessed using the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE). Serum was collected preoperatively and CSF at the onset of spinal anesthesia. AA in serum (SAA) and CSF samples was determined according to a muscarinic radio receptor bioassay. The association between AA measures and delirium was evaluated using logistic multivariate analyses. Results Fifty‐two (54%) of the participants in Oslo and 20 (39%) in Edinburgh developed delirium. There was no statistically significant difference in AA between participants with and without delirium in Oslo (serum: 7.02 vs 6.08 pmol/mL, P = .54; CSF: 0.39 vs 0.48 pmol/mL, P = .26) or in Edinburgh (serum: 1.35 vs 1.62 pmol/mL, P = .76; CSF: 0.36 vs 0.31 pmol/mL, P = .93). Nor was there any difference in SAA (Oslo, P = .74; Edinburgh, P = .51) or CSF AA (Oslo, P = .21; Edinburgh, P = .93) when participants were subdivided into prevalent, incident, subsyndromal, and never delirium. Stratifying participants according to prefracture cognitive status (IQCODE) gave the same results. Conclusion This is the first study of AA in CSF of individuals with and without delirium. The study does not support the hypothesis that central (CSF) or peripheral (serum) AA is an important mechanism of delirium in individuals with hip fracture.